2020
DOI: 10.1044/2019_jslhr-19-00176
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to Speech-Cue Weighting in Older Adults With Impaired Hearing

Abstract: Purpose In a previous paper ( Souza, Wright, Blackburn, Tatman, & Gallun, 2015 ), we explored the extent to which individuals with sensorineural hearing loss used different cues for speech identification when multiple cues were available. Specifically, some listeners placed the greatest weight on spectral cues (spectral shape and/or formant transition), whereas others relied on the temporal envelope. In the current study, we aimed to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Other approaches have attempted to identify why listeners with similar audiograms present substantial differences in suprathreshold performance. Recently, Souza et al (2020) showed how older HI listeners vary in terms of their ability to use specific cues (either spectral or temporal cues) for speech identification. Their results showed a so-called “profile cue” that characterizes the listener’s abilities in terms of spectro-temporal processing.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches have attempted to identify why listeners with similar audiograms present substantial differences in suprathreshold performance. Recently, Souza et al (2020) showed how older HI listeners vary in terms of their ability to use specific cues (either spectral or temporal cues) for speech identification. Their results showed a so-called “profile cue” that characterizes the listener’s abilities in terms of spectro-temporal processing.…”
Section: Discussionmentioning
confidence: 99%
“…1A bottom) before proceeding to the next trial (1 sec ITI). This 2-cue 2-AFC task, which is identical to the one used in Souza et al (2020), has the advantage that, unlike a two-interval or three-interval task, the target is always preceded and followed by a standard stimulus. This allows the task to be performed by comparing information either forward or backward in time.…”
Section: Methodsmentioning
confidence: 99%
“…Other approaches have attempted to identify why listeners with similar audiograms present substantial differences in suprathreshold performance. Recently, Souza et al (2020) showed how older HI listeners vary in terms of their use of specific cues (either spectral or temporal cues). The so-called profile cue characterizes the listener's predominant strategy for speech discrimination.…”
Section: Stratification In Hearing Research and Hearing Rehabilitationmentioning
confidence: 99%